JURIDICAL STUDY ON CHANGES IN THE LEGAL FORM OF REGIONAL COMPANIES (PD) BECOME A REGIONAL COMPANY (PERSERODA) (STUDY OF THE PLANNED CHANGE OF LHOKSEUMAWE REGIONAL DEVELOPMENT COMPANY STATUS) - Antary, Cut Rizki; Sunarmi, Sunarmi; Purba, Hasim (BULETIN KONSTITUSI, 2023)
This change in legal form is regulated by the Minister of Home Affairs Regulation No. 3 of 1998 concerning the Forms of BUMD and Government Regulation No. 54 of 2017 concerning BUMD. This research tries to examine the problems: the legal regulations change the legal form of a regional company to become a regional company, the factors that encourage the change in the legal form of a regional company to become a regional company and the legal consequences that arise on company assets after changing the legal form by referring to Law No. 23 of 2014 and Government Regulation No. 54 of 2017. The method used is normative legal research method. The nature of the research is descriptive. The type of data used is secondary data sourced from primary, secondary and tertiary legal materials. Secondary data were collected using literature study techniques and field studies with data collection tools in the form of interviews. Furthermore, these data were analyzed using qualitative analysis. The results show that the legal regulations changing the legal form of a regional company to a regional company have been regulated in Ministerial Regulation No. 3 of 1998 concerning Forms of BUMD and Government Regulation No. 54 of 2017 concerning BUMD. Meanwhile, the factors that led to the change in the legal form of a regional company to become a regional company were encountered, namely too much intervention from the government, no separation of political interests and economic interests, the lack of interest from other investors, and a lack of competent human resources. Based on the analysis of the change in the legal form of a regional company to a regional company, there is a legal vacuum on the accountability of asset management after changing the legal form.Keywords: local companies, regional companies, legal form..